Micro-Hydro Power Plants (MHPP): Technical and analytical studies in creating experimental learning media for physics students - Zuffa Anisa; Anggun Apprianda; Herta Novianto; Indriyani Rachman (Universitas PGRI Kanjuruhan Malang, 2021)
Nowadays, direct media use in learning energy is rarely found. Therefore, the authors intended to design a mini micro-hydro power plant (MHPP) in order to give direct experiences to students. This study generally aims to develop a mini MHPP consisting of equipment design, component selection, and the MHPP assembly. A test on discharge, heights, and produced power is then conducted. The data acquired are then analyzed in terms of either Pteotirik or Preal power using a predetermined equation. An analysis to the factors influencing the P values is then carried out. The power input of resulted from the water discharge management is 35.64 mW, while that of the power output is 9,61 mW. The efficiency of the MHPP set is by 26.96% which is considered quite low due to such factors as turbine blades, penstock pipes, generators, and the shift from water potential energy to other types of energies which is inevitable. It is expected that the developed mini MHPP is applicable as practicum learning media giving a lot of such learning experiences to students as to identify how hydroelectric power plant is, how the water energy shifts into electric energy, how high the electricity produced is, and to analyze factors influencing how high and low the electricity produced by a power plant.